Evaluation of Threats to Agriculture in the Totaré River Due to Changes in Rainfall Patterns Under Climate Change Scenarios - Duarte Prieto, Freddy Santiago; Jordi Rafael, Palacios Gonzalez; Germán Ricardo, Santos Granados (Ed. Springer Publishing Company, 2018)
In this paper we analyze the implications of different representative concentration pathway scenarios (RCP2.6, RCP4.5 and RCP8.5) on the precipitation of the Totaré River basin located in the Department of Tolima, Colombia, and its possible consequences on the productive systems of the area. In the analysis, we employed the global climatic model MPI-ESM-MR with 22 pluviographic stations of the IDEAM and the CSD (Chaotic Statistical Downscaling), a novel downscaling model for different intervals of accumulation of precipitation (5, 7, 10, 15 and 30 days). The results predict an increase of the precipitation in the Totaré River Basin from 10% to 50% for the middle and end of the century under all RCP scenarios. It is necessary to take measures to ensure adequate agricultural production due to possible flooding or soil erosion.

En este trabajo se analizan las implicaciones de diferentes escenarios de vías de concentración representativas (RCP2.6, RCP4.5 y RCP8.5) sobre la precipitación de la cuenca del río Totaré ubicada en el departamento del Tolima, Colombia, y sus posibles consecuencias sobre los sistemas productivos de la zona. En el análisis se empleó el modelo climático global MPI-ESM-MR con 22 estaciones pluviográficas del IDEAM y el CSD (Chaotic Statistical Downscaling), un novedoso modelo de downscaling para diferentes intervalos de acumulación de precipitación (5, 7, 10, 15 y 30 días). Los resultados predicen un aumento de la precipitación en la cuenca del río Totaré del 10% al 50% para mediados y finales de siglo bajo todos los escenarios RCP. Es necesario tomar medidas para garantizar una producción agrícola adecuada debido a las posibles inundaciones o a la erosión del suelo.
Keywords: Agricultura; Precipitación; Agriculture; Precipitation; GCM; Agricultura; Precipitación; GCM